'Absent' pulmonary valve with intact ventricular septum mimicking tricuspid valve atresia: Prenatal diagnosis and postnatal course. Issue 3 (17th January 2019) - Monacci, Francesca; Bondi, Tommaso; Canessa, Clementina; Chiappa, Enrico
Abstract: Absent pulmonary valve syndrome is a rare congenital heart disease characterized by absent or rudimentary pulmonary valve leaflets and hypoplastic pulmonary annulus. The most common variant, associated with tetralogy of Fallot, implies dilatation of pulmonary branches and usually absent ductus arteriosus. Rarely, absent pulmonary valve occurs with intact ventricular septum: pulmonary branches are normally sized or mildly dilated and ductus arteriosus is usually patent. The rarest type is associated with intact ventricular septum and tricuspid atresia. A close connection has been raised between pulmonary regurgitation and development of tricuspid valve. We describe a case of prenatal diagnosed absent pulmonary valve with intact ventricular septum and patent ductus arteriosus in which severe pulmonary regurgitation caused reversible functional atresia of tricuspid valve. Postnatally, satisfactory biventricular circulation was obtained with inotropic support for a few days while ductus arteriosus closed spontaneously. At a 3‐year follow up the child is asymptomatic without therapy.